Onycocaris longirostris Bruce, 1980 (Crustacea: Decapoda: Pontoniinae), new to the Australian fauna - Bruce, A. J. (Zootaxa, 2012)
A heterosexual pair of specimens of Onycocaris longirostris Bruce, 1980, previously known only from the single incompletemale holotype from New Caledonia, are reported from the Kimberley region of Western Australia. With the male major secondpereiopod and both female second pereiopods, these intact specimens enable the description of the species to be completed. A new record for Australian waters, it increases to 8 the number of Onycocaris species known from Australia.